Higher Education for Police Professionals. The Dutch Case. (6th December 2018) - Huisjes, Henk; Engbers, Fiona; Meurs, Teun
Abstract: In the Netherlands, already for some 20 years, a discourse on the relevance and nature of higher education for police professionals can be traced. To explain this discourse, the article consists of a reconstruction of the trajectory of change and an assessment of the current situation. Furthermore, a future perspective is included, which largely runs parallel with other forms of higher education for professions in the public sector. Key concepts, for instance, are the 'reflective practitioner' and the 'hybrid professional'. Also, a case is presented on the education of reflective practices, which exemplifies a didactics of teaching and learning in police practice. More than ever a close cooperation between police practice and police education is needed, as well as a clear focus on how 'learning by doing' relates to the need of a solid knowledge base. Together, teachers and practitioners may challenge the student to develop a personal judgment on the connection between theories (concepts, words) and practice (experience, works).